Nitrogen effect on zinc biofortification of maize and cowpea in Zimbabwean smallholder farms. (14th April 2020) - Manzeke, Muneta G.; Mtambanengwe, Florence; Watts, Michael J.; Broadley, Martin R.; R. Murray, Lark; Mapfumo, Paul
Abstract: Agronomic biofortification of crops with zinc (Zn) can be enhanced under increased nitrogen (N) supply. Here, the effects of N fertilizer on grain Zn concentration of maize ( Zea mays L.) and cowpea ( Vigna unguiculata L.) were determined at two contrasting sites in Zimbabwe over two seasons. All treatments received soil and foliar zinc‐sulphate fertilizer. Seven N treatments, with three N rates (0, 45, and 90 kg ha −1 for maize; 0, 15, and 30 kg ha −1 for cowpea), two N forms (mineral and organic), and combinations thereof were used for each crop in a randomized complete block design ( n = 4). Maize grain Zn concentrations increased from 27.2 to 39.3 mg kg −1 across sites. At 45 kg N ha −1, mineral N fertilizer increased maize grain Zn concentration more than organic N from cattle manure or a combination of mineral and organic N fertilizers. At 90 kg N ha −1, the three N fertilizer application strategies had similar effects on maize grain Zn concentration. Co‐application of N and Zn fertilizer was more effective at increasing Zn concentration in maize grain than Zn fertilizer alone. Increases in cowpea grain Zn concentration were less consistent, although grain Zn concentration increased from 39.8 to 52.7 mg kg −1 under optimal co‐applications of N and Zn. Future cost/benefit analyses of agronomic biofortification need to include information on benefits of agro‐fortified grain, complex farmer management decisions (including cost and access to both N and Zn fertilizers), as well as understanding of the spatial and site‐specific variation in fertilizer responses.